Ca(2+)-dependent and -independent interactions of the isoforms of the α(1A) subunit of brain Ca(2+) channels with presynaptic SNARE proteins - Kim, D. Kyle (The National Academy of Sciences of the USA, 1997)
Fast neurotransmission requires that docked synaptic vesicles be located near the presynaptic N-type or P/Q-type calcium channels. Specific protein–protein interactions between a synaptic protein interaction (synprint) site on N-type and P/Q-type channels and the presynaptic SNARE proteins syntaxin, SNAP-25, and synaptotagmin are required for efficient, synchronous neurotransmitter release. Interaction of the synprint site of N-type calcium channels with syntaxin and SNAP-25 has a biphasic calcium dependence with maximal binding at 10–20 μM. We report here that the synprint sites of the BI and rbA isoforms of the α(1A) subunit of P/Q-type Ca(2+) channels have different patterns of interactions with synaptic proteins. The BI isoform of α(1A) specifically interacts with syntaxin, SNAP-25, and synaptotagmin independent of Ca(2+) concentration and binds with high affinity to the C2B domain of synaptotagmin but not the C2A domain. The rbA isoform of α(1A) interacts specifically with synaptotagmin and SNAP-25 but not with syntaxin. Binding of synaptotagmin to the rbA isoform of α(1A) is Ca(2+)-dependent, with maximum affinity at 10–20 μM Ca(2+). Although the rbA isoform of α(1A) binds well to both the C2A and C2B domains of synaptotagmin, only the interaction with the C2A domain is Ca(2+)-dependent. These differential, Ca(2+)-dependent interactions of Ca(2+) channel synprint sites with SNARE proteins may modulate the efficiency of transmitter release triggered by Ca(2+) influx through these channels.